Naturalism and democracy : a commentary on Spinoza's political treatise in the context of his system - Bartuschat, Wolfgang,; Kirste, Stephan,; Walther, Manfred, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2019, ISBN: 9789004390898., 2019)
Naturalism and Democracy , first published in German in 2014, presents a long-awaited commentary on Spinoza's Political Treatise (Tractatus politicus) . Its contents reflect a recent intensification in the interest in Spinoza's political philosophy in Germany. The volume addresses Spinoza's political philosophy according to its place within his philosophical system as a whole, beginning with his theory of the natural genesis of law and state. Following from this are commentaries on the foundations of political philosophy, the relation of natural and state law, the theory of sovereignty, and theory of international relations. These chapters lay the basis for four essays interpreting Spinoza's attempt to conceive of a systematic optimization of political and legal institutions for all three forms of governance (monarchy, aristocracy, democracy). The volume closes with an analysis of the current relevance of Spinoza's political thinking and his influence on contemporary debates.